2017
DOI: 10.3324/haematol.2017.178103
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and survival of myeloma patients diagnosed 2008–2015. Real-world data on 4904 patients from the Swedish Myeloma Registry

Abstract: Epidemiology and outcome of myeloma are mainly reported from large university centers and collaborative groups, and do not represent ‘real-world’ patients. The Swedish Myeloma Registry is a prospective population-based registry documenting characteristics, treatment and outcome in newly diagnosed myeloma, including asymptomatic and localized forms, with the purpose of improving disease management and outcome. This report presents information on patients diagnosed between 2008 and 2015, including data on first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
124
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(144 citation statements)
references
References 31 publications
(25 reference statements)
15
124
4
1
Order By: Relevance
“…Consistent with results from both international population studies and NZ cancer registry data, patients in the later cohort had a significantly increased OS. The 5‐year relative survival of the later cohort (49%) was similar to that reported in the most recent population data from Australia (49%), the United States (51%) and Sweden (51%) . The Swedish data are of particular relevance as they cover a similar time period and, in common with NZ, frontline use of bortezomib or thalidomide was standard of care with a high level of NA use …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Consistent with results from both international population studies and NZ cancer registry data, patients in the later cohort had a significantly increased OS. The 5‐year relative survival of the later cohort (49%) was similar to that reported in the most recent population data from Australia (49%), the United States (51%) and Sweden (51%) . The Swedish data are of particular relevance as they cover a similar time period and, in common with NZ, frontline use of bortezomib or thalidomide was standard of care with a high level of NA use …”
Section: Discussionsupporting
confidence: 85%
“…Population studies of MM have consistently reported increased OS in recent decades, with these increases being attributed to the increased use of NA . In the current study, the survival outcomes of patients diagnosed and treated before and after the introduction of bortezomib were compared.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Because the average age of onset is 70–75 years, multiple myeloma is mainly a disease of the elderly and it has a steep increase in incidence with advancing age (23). The incidence of multiple myeloma is about 1.5 times higher in males than in females (4). Specifically, in the U.S., the 2011–2012 incidence of multiple myeloma (adjusted to the US standard population) was 7.8 per 100,000 person-years and 5.1 per 100,000 person-years for males and females, respectively (5).…”
Section: Introductionmentioning
confidence: 99%